2013
DOI: 10.2500/ajra.2013.27.3865
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Function in Healthy Children: Normative Data for Odor Identification

Abstract: In a general population-based sample of children, normative data of the Sniffin' Sticks screenings test are supplied as well as possible determinants of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 21 publications
11
36
0
Order By: Relevance
“…Therefore it was not possible to study any effects of interval lengths on the outcome of the reliability. In line with previous findings the BMI (BMI-Z-score) of children had no effect on the odor identification performance [8]. It has to be considered that in our study only four children had a BMI-Z-score of ±2 from the mean.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore it was not possible to study any effects of interval lengths on the outcome of the reliability. In line with previous findings the BMI (BMI-Z-score) of children had no effect on the odor identification performance [8]. It has to be considered that in our study only four children had a BMI-Z-score of ±2 from the mean.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is plausible that a 14-item odor identification test exhibits similar qualities. Whether women outperform men in odor identification tests has been controversially debated [3], [8]. In line with previous studies no sex difference was found in the current study in odor identification scores [3], [16], [18], [20].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations